ANALYSIS OF SCIENCE MATERIALS SOCIALIN MI/SD, CONFORMITY OF CHARATERISTICS, HOTS, AND 4C - Yuliananingsih, Yuliananingsih (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2021)
Abstract: Teaching material is an important learning element, it gets the attention of the teacher so that students can learn the things needed to achieve learning goals. This analysis aims to determine the suitability of class IV thematic textbooks with the Ministry of Education and Culture regulation Number 21 of 2016, the scope of social studies material. The suitability of textbooks with the characteristics of students and the literacy contained therein. The results of the analysis show: 1) Based on the content standards contained in the Regulation of the Minister of Education and Culture Number 21 of 2016, Class IV Thematic textbooks published by the Ministry of Education and Culture have met the predetermined standards. 2) it is in accordance with the development of students both in terms of material presentation, writing and image portions in the textbook. 3) there is no HOTS in the whole learning theme. 4) and there is financial literacy, culture and citizenship and character education. Keywords: Teaching materials, thematic textbooks, social studies material.